2019
DOI: 10.1051/0004-6361/201935784
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the chromospheric three-minute oscillations in sunspot umbrae

Abstract: Context. Sunspot umbrae show a change in the dominant period of their oscillations from five minutes (3.3 mHz) in the photosphere to three minutes (5.5 mHz) in the chromosphere. Aims. In this paper, we explore the two most popular models proposed to explain the three-minute oscillations: the chromospheric acoustic resonator and the propagation of waves with frequency above the cutoff value directly from lower layers. Methods. We employ numerical simulations of wave propagation from the solar interior to the co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 61 publications
(92 reference statements)
1
23
0
Order By: Relevance
“…This led Khomenko & Collados (2015) to conclude that there is no strong observational support for an umbral resonance cavity model of any kind. By employing numerical simulations of wave propagation, Felipe (2019) investigated the propagating wave model and the chromospheric resonator model together, and concluded that the propagating wave model can explain the dominant period of the three-minute oscillations even without the chromospheric resonator, but the chromospheric resonator strongly enhances the power of the three-minute oscillations if it exists.…”
Section: Introductionmentioning
confidence: 99%
“…This led Khomenko & Collados (2015) to conclude that there is no strong observational support for an umbral resonance cavity model of any kind. By employing numerical simulations of wave propagation, Felipe (2019) investigated the propagating wave model and the chromospheric resonator model together, and concluded that the propagating wave model can explain the dominant period of the three-minute oscillations even without the chromospheric resonator, but the chromospheric resonator strongly enhances the power of the three-minute oscillations if it exists.…”
Section: Introductionmentioning
confidence: 99%
“…The umbral 3 min waves observed in the chromosphere were shown to be already present in the photosphere in a study by [ 28 ]. Numerical simulations [ 56 ] aided in the conclusion that propagation of waves in the 3 min band directly from the photosphere can explain the observed chromospheric 3 min oscillations. So it is not shocking to see the 3 min power, the surprising part is that it appears in the magnetogram data.…”
Section: Discussionmentioning
confidence: 99%
“…Their power is reduced with frequency as a result of the rapid decrease with frequency of the incident wave power from subphotospheric layers5 . Several numerical simulations of chromospheric resonances above sunspot umbrae also show no trace of a power increase at high frequencies6,8 . On the contrary, the paper by Jess et al identifies this power increase as a signature of the chromospheric…”
mentioning
confidence: 97%
“…They show an enhanced power and a shorter dominant period, from waves with an amplitude of a few hundred meters per second in the five-minute band at the photosphere, to amplitudes of several kilometers per second in the three-minute band at the chromosphere. Various models have been proposed to explain this behaviour [1][2][3] , including the presence of a chromospheric resonance cavity between the photosphere and the transition region [4][5][6][7][8] . Jess et al 9 claimed the detection of observational evidence supporting this model, obtained from the comparison of spectropolarimetric observations and numerical simulations.…”
mentioning
confidence: 99%